Efficiency evaluation of water absorbing polymers on after planting coffee plant growth - Vale, Geraldo Fernando Rezende do; Carvalho, Samuel Pereira de; Paiva, Leandro Carlos (Coffee Science - ISSN 1984-3909, 1970)
<!-- @page { size: 8.5in 11in; margin: 0.79in } P { margin-bottom: 0.08in } --> A water absorbent polymer can guarantee plant water supply in regions presenting water deficits. Stockosorb® is an inert acrylic polymer that transforms into a gel when it absorbs water and can later gradually release this water to plants. This research was aimed at studying the effects of the water-holding polymer Stockosorb®, associated or not to organic matter, upon the initial field development of coffee (cv. Catucaí) seedlings. A randomized block design was utilized, in a 2 x 2 x 3 factorial arrangement with four replications totalizing 12 treatments. The following factors were considered: a) two planting systems (SP) (no tillage and conventional); b) two organic matter dosages (MO) (no organic matter and 500 grams per hole); c) three polymer dosages (DP) (no polymer, 3.0, and 6.0 grams per hole). The polymer, in a powdered form, was appplied to the holes before seedling planting. The experiment was carried out at Univesidade Federal de Lavras, in Minas Gerais, Brazil. Planting systems showed significant effect, however, the dosages of organic matter and polymer did not effect the initial plant development.